A Systematic Review of Gender-Based Violence Prevention and Response Interventions for HIV Key Populations: Female Sex Workers, Men Who Have Sex With Men, and People Who Inject Drugs. (April 2022) - Decker, Michele R.; Lyons, Carrie; Guan, Kathleen; Mosenge, Vanessa; Fouda, Ghislane; Levitt, Daniel; Abelson, Anna; Nunez, Gnilane Turpin; Njindam, Iliassou Mfochive; Kurani, Shaheen; Baral, Stefan
Gender-based violence (GBV) is that perpetrated based on sex, gender identity, or perceived adherence to socially defined gender norms. This human rights violation is disproportionately experienced by HIV key populations including female sex workers (FSW), people who inject drugs (PWID), and men who have sex with men (MSM). Consequently, addressing GBV is a global priority in HIV response. There is limited consensus about optimal interventions and little known about effectiveness. Our systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and was registered in International Prospective Register of Systematic Reviews. Peer-reviewed and non-peer-reviewed literature were searched for articles that described a GBV prevention or response intervention specifically for key populations including FSW, PWID, and MSM. Results were organized by level(s) of implementation and pillars of a comprehensive GBV response: prevention, survivor support, and accountability/justice. Of 4, 287 articles following removal of duplicates, 32 unique interventions (21 FSW, seven PWID, and nine MSM, not mutually exclusive) met inclusion criteria, representing 13 countries. Multisectoral interventions blended empowerment, advocacy, and crisis response with reductions in violence. Individual-level interventions included violence screening and response services. Violence-related safety promotion and risk reduction counseling within HIV risk reduction programming reduced violence. Quantitative evaluations were limited. Violence prevention and response interventions for FSW, PWID, and MSM span individual, community, and multisectoral levels with evidence of promising practices at each level. The strongest evidence supported addressing violence in the context of sexually transmitted infection/HIV risk reduction. As interventions continue to emerge, the rigor of accompanying evaluations must simultaneously advance to enable clarity on the health and safety impact of GBV prevention and response programming.